2020
DOI: 10.1371/journal.pone.0229653
|View full text |Cite
|
Sign up to set email alerts
|

Investigating influence factors of traffic violations at signalized intersections using data gathered from traffic enforcement camera

Abstract: To effectively reduce traffic violations that often cause severe crashes at signalized intersections, exploring their contributing factors seems hugely urgent and essential. This study attempted to investigate the influence factors of wrong-way driving (WWD), red-light-running (RLR), violating traffic markings (VTM), and driving in the inaccurate oriented lane (DIOL) at signalized intersections by using data collected from traffic enforcement camera in Hohhot, China. To this end, an ordinary multinomial logit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 44 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Video image processing techniques and RADAR sensors (or sets of different sensors including image capture connected to a traffic signal controller) are often used to detect or predict traffic violations. For instance, when a vehicle exceeds the speed limit, as well as when a vehicle crosses the stop line at a junction or at a pedestrian crossing when red signals are displayed [ 90 , 91 ]. Information on the scale of the violations may be taken into account when assessing the safety of selected elements of the road system.…”
Section: Simulation Methods Of Road Safety Assessmentmentioning
confidence: 99%
“…Video image processing techniques and RADAR sensors (or sets of different sensors including image capture connected to a traffic signal controller) are often used to detect or predict traffic violations. For instance, when a vehicle exceeds the speed limit, as well as when a vehicle crosses the stop line at a junction or at a pedestrian crossing when red signals are displayed [ 90 , 91 ]. Information on the scale of the violations may be taken into account when assessing the safety of selected elements of the road system.…”
Section: Simulation Methods Of Road Safety Assessmentmentioning
confidence: 99%
“…Higher temperatures may lead to reduced vigilance and inattention which directly resulted in the poor driving behaviors ( 32–35 ). At the same time, high temperatures may increase the likelihood of dangerous behaviors such as running red lights and driving in the wrong lane ( 36 ). In addition, changes in ambient temperatures may also result in the occurrence of disease, which increased the risk of traffic accidents for road users when they traveled ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jantosut et al [7] found traffic violations by motorbike drivers to be more common in driving environments with short cross distances, high traffic volumes, and at night. Likewise, a study by Fu & Liu [21] found that incomplete infrastructure also plays a role in the courage of drivers to violate traffic. A study by Sasaki et al [23] find that most traffic violations occur on wider, straighter and segregated roads, where infrastructure increases overconfidence.…”
Section: Factor Affectingmentioning
confidence: 96%